Investigating the views and expectations of pregnant women who undergo genetic counselling for age-related risk of aneuploidy - Vorster, Nina (Department of Clinical Laboratory Sciences, 2021)
Background: Pregnancy at advanced maternal age (AMA) is associated with an increased risk of aneuploidy. In the Western Cape's public health sector maternal age alone is widely used to screen women for high risk of pregnancies affected by aneuploidy. The weekly pregnancy counselling clinic (PCC) at Groote Schuur Hospital (GSH) offers genetic counselling (GC) for women who are of AMA to inform them about their age-related aneuploidy risk, offer invasive diagnostic testing (IDT) and discuss the option of voluntary termination of an affected pregnancy. A recent audit at GSH showed that the uptake of IDT was low and other literature reports that South Africans tend to have a conservative view regarding termination of pregnancy (TOP). This study sought to understand what women expect from the GC service at PCC as well as what their experiences are of the service. Methods: This qualitative phenomenological study used a pragmatic approach and participants were recruited through purposive sampling. Semi-structured, in-person interviews were conducted after women had completed their GC sessions at PCC. Thematic analysis was used to analyse the data. Results: The results of this study suggest that participants (n=7) received very little information about their GC appointments at referring clinics, and that they generally did not have prior knowledge about age-related aneuploidy risks. Finding out about the age-related risk of aneuploidy was an emotional experience for the participants, but other factors, including normal ultrasound results, provided relief. The participants' choices regarding IDT and attitudes towards TOP reflected that of available literature as the uptake was low and most participants reported that they would not consider a TOP. The women reported that they would use the knowledge they gained during GC to educate other women in their communities about the pregnancy risks associated with increased maternal age. Generally, the participants believed that GC was useful and appreciated the opportunity. Conclusion: The participants in this study had limited health literacy and knowledge regarding AMA risks and GC. As a result, participants had no expectations of GC. However, the participants felt that GC was useful in helping them prepare for the possibility of a child with DS, and generally viewed the service in a positive light. Additionally, this study's results suggests that there is a need to educate women in local communities regarding AMA pregnancy risks.